Alternative means of recycling pineapple leaf residues - Ahmed, Osumanu H.; Husni, Ahmad M.H.; Anuar, Rahin A.; Hanafi, Mohamed M. (International Society for Horticultural Science, 2003)
Introduction. One of the challenges of the Malaysian pineapple industry is to develop new techniques for managing pineapple residues. A study was carried out to investigate whether K-humate can be produced from these residues. Materials and methods. Pineapple leaves were air-dried, shredded and chipped. Some of the shredded leaves were incinerated at 500 °C. Potassium hydroxide (KOH) was extracted by dissolving the ash obtained in distilled water for 24 h at a ratio of 1:7 (ash/water) after which the sample was filtered. After this extraction of KOH from the ashes of pineapple leaf residues, the remaining ash residues were further analyzed to assess the total and soluble K contents. Moreover, a given quantity of shredded leaf residues was mixed with chicken dung (as a source of microorganisms and nitrogen) and chicken feed. The mixture was composted with standard procedures. Humic acids were reconstituted using KOH from pineapple leaves with K from ash residues and K from composted pineapple leaves. Results and discussion. By reconstituting humic acids with KOH, a K-humate was produced with approximately 34.5% of its K readily soluble in water. A reconstitution of humic acids with K from ash residues produced a K-humate with approximately 3.34% of its K readily soluble in water. Conclusion. The K-humate produced from the reconstitution of humic acids with K from KOH can be used in fertigation programmes as a source of K while the K-humate produced through the reconstitution of humic acids with K from ash residues can be used as a source of K for fresh water fishes.